Dualità nomiche (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2015)
This article examines some juridical and political aspects of Sofokles’ Antigone, and especially the opposition between the ágrapta nómima called into play by Antigone and the kérygma issued by Creontes. The author analyzes the real meaning of this contrast in the Sofokles’ age and in the structure of his tragedy, because many interpretations by the different scholars (ius versus lex; nómos versus tyrannical order; natural law versus positive law etc.) seem anachronistic or not very plausible. We can find an explanation not only in the rich semantic field of the word nómos (still) in the V century B.C., but also in the various dualities typical of the Antigone.Quest’articolo esamina alcuni aspetti giuridici e politici dell’Antigone di Sofocle, e in particolare l’opposizione tra gli ágrapta nómima chiamati in causa da Antigone e il kérygma disposto da Creonte. L’autore analizza il reale significato di questo contrasto nell’età di Sofocle e nella struttura della sua tragedia, dal momento che molte interpretazioni degli studiosi (ius versus lex; nómos versus ordine di un tiranno; diritto naturale versus diritto positivo etc.) appaiono anacronistiche o poco plausibili. Possiamo trovare una spiegazione non solo nel ricco campo semantico del termine nómos (ancora) nel V secolo a.C., ma anche nelle varie dualità che sono caratteristiche dell’Antigone.